Work From Home, Mental Health and Employee Needs: A pilot study in selected information technology organizations in India - Phadnis S.; Sengupta S; Chakraborty A (ACHSM, 2021)
Introduction: The Coronavirus (COVID-19) pandemic has impacted the economy and has resulted in changes to the working arrangements of employees who are based at home and may continue to work from home (WFH). Organizations are expected to develop an inclusive policy for their employees to promote mental health whilst working from home. The aim of this study was to document the impact of WFH on mental health and determine the expectations of employees from their organizations regarding occupational health policy. Methodology: A cross-sectional study was conducted on the impact of work from home on mental health and to document the mental health support needs of employees. Google form was floated through social media platform to receive the responses. A total of 74 responses were received. Descriptive analysis was conducted using Microsoft Excel, while qualitative answers were manually analysed. Results: About 67% employees (n=45) mentioned that their workload has increased significantly during work from home. Thirty five percent (n=26) felt lonely and lost and 47% (n= 34) felt disconnected from the real world, indicating the mental health impact of work from home. Fifty three percent employees (n=40) mentioned that there were no efforts made by their organization to reduce the mental health impact of work from home. Conclusion: The results of this study indicate that there is an urgent need to create a comprehensive occupational health and safety policy inclusive of strategies to improve mental health by the organizations in light of "work from home" as a "new-normal".